The role of agents in accounting reform in the face of the institutional change: The case of the Colegio Universidad de Osuna (1775-1824) - Jesús D. López-Manjón; Fernando Gutiérrez-Hidalgo (Revista de Contabilidad: Spanish Accounting Review, 2023)
This study aims at enriching literature on accounting change by studying the role of the agents in the accounting reform of the Colegio Universidad de Osuna (CUO, College and University of Osuna) in the last quarter of the eighteenth century. The paper explores how, in the period 1775-1777, the CUO modified its rules, including its accounting procedures, to prevent its disappearance. Those modifications were aimed at aligning the CUO with the new Enlightenment institutional framework regarding academic requirements and economic rationality. The visitor who prepared the new rules, Miguel Benito Ortega, played a central role in this process. The paper explores the circumstances that favored Ortega's role as an agent of change and those that caused the brief and incomplete application of its rules, which contributed to CUO surviving some years but that it would be closed definitively in 1824.